2022
DOI: 10.1111/jonm.13532
|View full text |Cite
|
Sign up to set email alerts
|

Structural empowerment and work ethics influence on the work engagement of millennial nurses

Abstract: Aim: This study investigated the influence of structural empowerment and work ethics on work engagement among millennial Saudi clinical nurses. Background: No extensive research has been conducted on the structural empowerment, work ethics and work engagement of millennial nurses, especially in Arab countries such as Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 39 publications
(68 reference statements)
2
27
0
Order By: Relevance
“…This study showed that there is a significant positive correlation between vocational delay of gratification and work engagement and that vocational delay of gratification is a significant predictor of work engagement, which confirms the findings of existing studies (Xanthopoulou et al, 2009;Balay-Odao et al, 2021;Liu and Wang, 2021;Zhang et al, 2022). Studies from Shi et al (2021) suggested that vocational delay of gratification, on the one hand, brings positive emotions and helps individuals to expand their awareness and attention, thus making them more focused and dedicated to the work at hand, and on the other hand, increases work engagement by reducing rumination and attention associated with negative emotions.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that there is a significant positive correlation between vocational delay of gratification and work engagement and that vocational delay of gratification is a significant predictor of work engagement, which confirms the findings of existing studies (Xanthopoulou et al, 2009;Balay-Odao et al, 2021;Liu and Wang, 2021;Zhang et al, 2022). Studies from Shi et al (2021) suggested that vocational delay of gratification, on the one hand, brings positive emotions and helps individuals to expand their awareness and attention, thus making them more focused and dedicated to the work at hand, and on the other hand, increases work engagement by reducing rumination and attention associated with negative emotions.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Chan et al, [ 36 ] demonstrated that work engagement is related to being married. According to Balay‐odao et al,’s [ 106 ] research, marital status influences work engagement of millenial Saudi clinical nurses. It is discovered that married millenial Saudi nurses showed better dedication than single nurses.…”
Section: Discussionmentioning
confidence: 99%
“…It is discovered that married millenial Saudi nurses showed better dedication than single nurses. In addition, the reason for the high work engagement among married people is deemed to be originated by accountability, high involvement in work and emotional stability of married people and the extra support that they get from their families [ 106 ]. In a similar study conducted after the onset of the Covid-19 pandemic, considerably higher work engagement was noticed in people who were married or living with a partner, with children under 16 years of age, and with a very good perception of health in the last 14 days [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations